Serum RNA Profiling in the 10-Years Period Prior to Diagnosis of Testicular Germ Cell Tumor - Burton, Joshua; Umu, Sinan U.; Langseth, Hilde; Grotmol, Tom; Grimsrud, Tom K.; Haugen, Trine B.; Rounge, Trine B. (Frontiers in Oncology, 2020)
Although testicular germ cell tumour (TGCT) overall is highly curable, patients may experience late effects after treatment. An increased understanding of the mechanisms behind the development of TGCT may pave the way for better outcome for patients. To elucidate molecular changes prior to TGCT diagnosis we sequenced small RNAs in serum from 69 patients who were later diagnosed with TGCT and 111 matched controls. The deep RNA profiles, with on average 18 million sequences per sample, comprised of nine classes of RNA, including microRNA. We found that circulating RNA signals differed significantly between cases and controls regardless of time to diagnosis. Different levels of TSIX related to X-chromosome inactivation and TEX101 involved in spermatozoa production are among the interesting findings. The RNA signals differed between seminoma and nonseminoma TGCT subtypes, with seminoma cases showing lower levels of RNAs and nonseminoma cases showing higher levels of RNAs, compared with controls. The differentially expressed RNAs were typically associated with cancer related pathways. Our results indicate that circulating RNA profiles change during TGCT development according to histology and may be useful for early detection of this tumour type.